PENAKSIR RASIO REGRESI LINEAR YANG EFISIEN UNTUK RATA-RATA POPULASI PADA SAMPLING ACAK SEDERHANA - Dakhyu, Ratni; Efendi, Rustam; Sirait, Haposan (Jurnal Online Mahasiswa (JOM) Bidang Matematika dan Ilmu Pengetahuan Alam, 2015)
In this article we study three linear regression ratio estimators for the population mean on simple random. This study is a review of the article of Singh, et. al [Statistics in Transition-new series, 10: 85-100]. Each estimator is a biased estimator and their mean square errors are determined. Estimator with the smallest mean square error is the most efficient one. An example is given at the end of the discussion.